(untitled) (Annual of the Faculty of Philosophy in Skopje, 2017)
The moral discipline of family and its relations have a central role in the discourse of the Catholic Church in Italy. The very idea of the family, marriage and its status, divorce, abortion and forms of family planning, as well as relations between men and women are critical for the morality of the Catholic family. Italy is perceived as a traditionally Catholic country, however, in the past few decades, it was not immune to the impact of social processes, such as globalization, individualism and materialism, which led to a decline in the number of followers, reduced spirituality, family crisis and change of the concept of unity. This paper analyses the role of the Catholic Church in the Italian society in the past and the present, focusing on major debates on forms of families, marriage, divorce and abortion. It gives an overview of the influence of the Church as an institution on the family in the contemporary society and examines ways the Catholic Church has shaped and defined the Italian family over the time.